ESP32-Based Ornamental Fish Feeding Automation System With Sensor Utilisation and Fuzzy Logic Implementation - Muhammad Hafidz Fachrezi; Darrell Juro Rudy Pradana; Aulia Najiha Putri; Aisyah Rahmadiniyah; Dhaifan Rahadhian; Shalfa Hafizh Sulaiman; Atikah Safitri Siregar (Batrisya Education, 2025)
The efficiency of ornamental fish feeding significantly influences fish health and water quality in aquaculture systems. Manual feeding often results in overfeeding or underfeeding, leading to water pollution and reduced fish productivity. This study aims to design and implement an automated ornamental fish feeding system using the ESP32 microcontroller integrated with temperature, pH, and dissolved oxygen sensors. The system employs Mamdani fuzzy logic to determine feeding quantities based on real-time environmental parameters. Research was conducted at the Aquaculture Production Laboratory and Hardware Laboratory 2, IPB University. The results show that the system is capable of dynamically adjusting feeding amounts, thereby reducing feed waste and maintaining water quality. The fuzzy logic approach allows for adaptive and efficient feeding management, outperforming fixed-timer systems. This automation technology supports sustainable and technology-driven ornamental fish farming.